PI3K‐Akt pathway enhances the differentiation of interleukin‐27‐induced type 1 regulatory T cells. Issue 3 (31st July 2017) - Nadya, Niken Adiba; Tezuka, Hiroyuki; Ohteki, Toshiaki; Matsuda, Satoshi; Azuma, Miyuki; Nagai, Shigenori
Summary: Interleukin 27 (IL‐27) has been identified as a potent cytokine in the differentiation of type 1 regulatory T (Tr1) cells through interactions with several key elements, including transcription factors such as aryl hydrocarbon receptor and IL‐21. Autocrine production of IL‐21 is known to be important for maintaining IL‐10 expression by Tr1 cells. Although previous studies have shown that the phosphoinositide 3‐kinase (PI3K) –Akt axis contributes to the differentiation of helper T‐cell subsets, the role of the PI3K pathway on Tr1 cell differentiation remains to be elucidated. Here, we demonstrate that suppression of the PI3K‐Akt pathway results in impairment of IL‐27‐induced Tr1 (IL‐27–Tr1) cell differentiation in vitro and in vivo . Furthermore, this suppression down‐regulates IL‐21 receptor expression by Tr1 cells, followed by suppression of IL‐10 expression by IL‐27–Tr1 cells. These results suggest that the PI3K pathway enhances IL‐10 expression by IL‐27–Tr1 cells through up‐regulation of IL‐21 receptors. Abstract : The inhibition of phosphoinositide 3‐kinase (PI3K) pathway suppresses interleukin‐10 (IL‐10) expression by IL‐27‐induced type 1 regulatory T (IL‐27–Tr1) cells and this inhibition negatively regulates IL‐21 receptor expression on IL‐27–Tr1 cells despite the abundance of IL‐21. We demonstrated the importance of the PI3K‐Akt pathway in the differentiation of IL‐27–Tr1 cells through the up‐regulation of IL‐21 receptors.